Pengembangan Kombucha Cengkeh dan Pandan Wangi serta Uji Aktivitas Antidepresan secara In Vivo terhadap Mencit Jantan - Alda Alfina; Anas Bagaskara Witanto; Abdullah Sirajuddin Sya'bana; Ajeng Daniarsih (Universitas Nusantara PGRI Kediri, 2026)
This study aims to develop a psychobiotic beverage based on kombucha infused with clove (Syzygium aromaticum) and pandan (Pandanus amaryllifolius), and to evaluate its potential antidepressant activity in vivo in male mice (Mus musculus). The organoleptic assessment was conducted on 30 panelists evaluating color, aroma, taste, and overall acceptance. The antidepressant test used the Forced Swim Test (FST) with three treatment groups: negative control (aquadest), positive control (amitriptyline 2 mg/200 g BW), and treatment group (clove–pandan kombucha 4 mL/200 g BW). Results showed high sensory acceptance with average scores for color = 4.07, aroma = 3.67, taste = 3.77, and overall = 3.80 (“attractive” category). The treatment group exhibited a 16.5% reduction in immobility time compared to the negative control, indicating a mild antidepressant effect. This activity is attributed to the presence of eugenol in clove and flavonoids in pandan, which enhance neurotransmitter balance and produce mild relaxation effects. The combination of probiotic fermentation and herbal bioactive compounds suggests that clove–pandan kombucha has potential as a natural psychobiotic functional drink supporting mental health and contributing to Sustainable Development Goal 3 (Good Health and Well-being).